Implementación de seguridades basadas en capas con tecnología cisco para mejorar la seguridad de la información y productividad de la empresa prodemco. s. a. en la provincia del Azuay, capital Cuenca en la calle Nicanor Aguilar y Luis Moreno mora en el período 2014 - 2015 - Vinocunga Viracocha, Carolina Elizabeth (2015)
This research is about an alternative of routing communications at Prodemco SA. with alternative configurations, which will help both: the fidelity of communications and securities, this create a nimble and entire information cycle. Routing data between networks that form the timber group has made possible the improvement of processes in other areas, in this case it has been realized through CISCO technology which is the best one currently on the telecommunications market; it took into account the securities for routing with network subnetting into subnets for getting a communication almost point by point arithmetic calculation network, then the network security is access control, the ability to limit and control access to host applications and systems through communications links. To determine which users are seeking access, they should be identified and authenticated before, so that the access rights can be adapted individually....